ANALISIS HIGHER ORDER THINKING SKILLS (HOTS) KELAS XI : PENGARUH MODEL FLIPPED CLASSROOM - Hidayah, Nur; Lestari, Puji; Handoko, Akbar; Bidayati Haka, Nukhbatul; Puspita, Laila; Oktina Sari Pratama, Annisa (Jurnal Biogenerasi, 2025)
Field studies show that students' higher order thinking skills (HOTS) are still low. This research aims to determine the impact of using the flipped classroom model on students' higher order thinking skills (HOTS). In its implementation, this research used a quasi-experimental method. There are two classes used, namely the control class and the experimental class, which were obtained using the cluster random sampling technique. The experimental class uses a flipped classroom model and the control class uses a exspository learning model. The instruments used in this research is test. The test instrument is to measure students' HOTS. Based on the results of the hypothesis test, the sig value is obtained. 0.000 < 0.05 so it can be seen that the flipped classroom model can be used to increase students' HOTS.